2004
DOI: 10.1007/s00066-004-1192-7
|View full text |Cite
|
Sign up to set email alerts
|

Positional Variability of a Tandem Applicator System in HDR Brachytherapy for Primary Treatment of Cervix Cancer

Abstract: Intraindividual applicator variability is significantly smaller than interindividual variability. Applicator-related procedures such as midline shielding or dose matching of tele- and brachytherapy should be performed with information on at least one individual applicator position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…To evaluate the influence of applicator displacement on the dose to the CTV and OARs, the applicators in the 2D-BT and 3D-BT plans were virtually moved in 3 directions: left (+ X ) or right (−X ), cranial (+ Y ) or caudal (− Y ), and anterior (+ Z), or posterior (−Z). Since most of the current studies reported displacement measurements of less than 1 cm in clinical practice, [9][10][11][16][17][18] we set the simulated shift distances as ± 0.15, ± 0.2, ± 0.4, ± 0.6, ± 0.8, and ± 1 cm in this study. After changing the spatial position of T&O, the dwell times and relative positions of the radiation sources in the applicators remained the same as those in the original plans for both 2D-BT and 3D-BT.…”
Section: Simulation Of Applicator Displacementmentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate the influence of applicator displacement on the dose to the CTV and OARs, the applicators in the 2D-BT and 3D-BT plans were virtually moved in 3 directions: left (+ X ) or right (−X ), cranial (+ Y ) or caudal (− Y ), and anterior (+ Z), or posterior (−Z). Since most of the current studies reported displacement measurements of less than 1 cm in clinical practice, [9][10][11][16][17][18] we set the simulated shift distances as ± 0.15, ± 0.2, ± 0.4, ± 0.6, ± 0.8, and ± 1 cm in this study. After changing the spatial position of T&O, the dwell times and relative positions of the radiation sources in the applicators remained the same as those in the original plans for both 2D-BT and 3D-BT.…”
Section: Simulation Of Applicator Displacementmentioning
confidence: 99%
“…Both target coverage and OAR sparing are then evaluated accurately in the brachytherapy treatment planning system (TPS). 7 In current practice, both brachytherapy techniques include the process of transferring the patient from the gynecological room to the X-ray/CT/MRI imaging room, and then to the brachytherapy room, which inevitably causes applicator displacement [8][9][10] even with an immobilization device. Wulf et al 10 investigated the intrafractional applicator displacement and found that the standard deviations (SD) of variability were 2.5 mm (minimum/maximum, − 17/ + 19 mm), 5.5 mm (minimum/maximum, − 21/+ 23 mm), and 4.2 mm (minimum/maximum, − 15/+ 18 mm) in the right-left (X-axis), caudal-cranial (Y-axis), and anterior-posterior (Z-axis) directions, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation